Correia, Antonia - (:unkn) unknown (My University, 2026)
Maria Antónia P. M. Correia works at the Open Access Projects’ Office of the Documentation Services of Universidade do Minho as information specialist, collaborating in FOSTERPlus and FIT4RRI projects. She has a BA in Anglo-Portuguese Studies by the Universidade Nova de Lisboa and attended two post-graduation courses in Library and Information Sciences (2004) and in Archives (2006) from the Universidade de Lisboa. She has more than 15 years of experience coordinating university libraries, and in recent years has developed support services for researchers in the areas of scientific publication, promotion of the researcher's visibility at a personal and institutional level and researcher’s assessment. In this context, she taught several training sessions, including the module on Scientific Publication in the course of Information Literacy, and she designed and coordinated the Research Data Management course at the Universidade Nova de Lisboa’s Doctoral School.